The emergence of sex differences in personality traits in early adolescence: A cross-sectional, cross-cultural study - De Bolle, Marleen; De Fruyt, Filip; McCrae, Robert R; Löckenhoff, Corinna E; Costa, Paul T; Aguilar-Vafaie, Maria E; Ahn, Chang-kyu; Ahn, Hyun-nie; Alcalay, Lidia; Allik, Jüri; Avdeyeva, Tatyana V; Bratko, Denis; et al. (Journal of personality and social psychology, 2015)
Although large international studies have found consistent patterns of sex differences in personality traits among adults (i.e., women scoring higher on most facets), less is known about cross-cultural sex differences in adolescent personality and the role of culture and age in shaping them. The present study examines the NEO Personality Inventory-3 (McCrae, Costa, & Martin, 2005) informant ratings of adolescents from 23 cultures (N = 4,850), and investigates culture and age as sources of variability in sex differences of adolescents' personality. The effect for Neuroticism (with females scoring higher than males) begins to take on its adult form around age 14. Girls score higher on Openness to Experience and Conscientiousness at all ages between 12 and 17 years. A more complex pattern emerges for Extraversion and Agreeableness, although by age 17, sex differences for these traits are highly similar to those observed in adulthood. Cross-sectional data suggest that (a) with advancing age, sex differences found in adolescents increasingly converge toward adult patterns with respect to both direction and magnitude; (b) girls display sex-typed personality traits at an earlier age than boys; and (c) the emergence of sex differences was similar across cultures. Practical implications of the present findings are discussed. (PsycINFO Database Record (c) 2015 APA, all rights reserved).
Keywords: dospělí; Female; dítě; Personality; Age Factors; srovnání kultur; Adolescent Development; Adult; mladý dospělý; ženské pohlaví; průřezové studie; Adolescent; věkové faktory; lidé; osobnost; Culture; kultura; Sex Characteristics; Sex Factors; vývoj mladistvých; Cross-Sectional Studies; Male; Aged; sexuální faktory; Young Adult; pohlavní dimorfismus; Cross-Cultural Comparison; lidé středního věku; Child; senioři; mužské pohlaví; Middle Aged; mladiství; Humans